1990
DOI: 10.1177/004051759006000107
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Water Vapor Resistance of Microporous and Hydrophilic Films with Relative Humidity

Abstract: A method is described for measuring the water vapor resistance of textiles under variable conditions of relative humidity (RH). It consists basically of varying the position of the sample in an air gap between a wet and a dry surface while keeping all other conditions constant. The resistance is determined by the rate of water loss from the apparatus and the temperature of the water. The results for microporous PTFE and polyurethane films show little variation with RH, but fabrics and films with hydrophilic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 4 publications
(3 reference statements)
2
40
0
Order By: Relevance
“…The analogy is to the water vapor sorption isotherm, which is the equilibrium water content of a hygroscopic polymer as a function of relative humidity. The mean relative humidity has proven to be useful in showing the mass transport behavior in terms of concentration dependence of the permeability coefficient [4,7,8]. Figure 4 shows the measured water vapor diffusion resistance of the three materials using the setpoints of Table 1.…”
Section: Example Of Concentration-dependent Diffusion In Membrane Lammentioning
confidence: 99%
See 3 more Smart Citations
“…The analogy is to the water vapor sorption isotherm, which is the equilibrium water content of a hygroscopic polymer as a function of relative humidity. The mean relative humidity has proven to be useful in showing the mass transport behavior in terms of concentration dependence of the permeability coefficient [4,7,8]. Figure 4 shows the measured water vapor diffusion resistance of the three materials using the setpoints of Table 1.…”
Section: Example Of Concentration-dependent Diffusion In Membrane Lammentioning
confidence: 99%
“…The diffusion resistance given in Figure 4 is the sum of the intrinsic material resistance (/?.) plus the boundary layer resistance (R b ), as defined in equation (4). In this report we present the combined resistances as a single value, but procedures exist for separately determining the intrinsic material mass transfer and boundary layer resistances [7,8].…”
Section: Example Of Concentration-dependent Diffusion In Membrane Lammentioning
confidence: 99%
See 2 more Smart Citations
“…The behaviour of these materials has been studied under various circumstances, as e.g. in different ambient humidities (Farnworth et al 1990), with condensation at its surface (Osczevski 1993), at various atmospheric pressures (Fukazawa et al 1999), and in various ambient temperatures (Finn et al 2000). Studies on the behaviour of such materials at low temperature, however, have shown that the vapour resistance of some of these materials increases dramatically when temperatures fall below zero degrees Celsius (Osczevski 1993(Osczevski , 1996.…”
Section: Introductionmentioning
confidence: 99%